2004
DOI: 10.1074/jbc.c300460200
|View full text |Cite
|
Sign up to set email alerts
|

Rip2 Participates in Bcl10 Signaling and T-cell Receptor-mediated NF-κB Activation

Abstract: Engagement of the T-cell receptor (TCR) initiates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 24 publications
3
83
1
Order By: Relevance
“…Moreover, the pan-PKC inhibitor GFX did not affect the Ser 138 -dependent initial phosphorylation of Bcl10 nor the TCR-induced F-actin increase, but showed an inhibitory effect on a second, as yet unidentified site of Bcl10 phosphorylation that is thus unlikely to be relevant for actin polymerization. The receptor-interacting protein (RIP) family kinase RIP2 has been shown to associate with Bcl10 and to induce its phosphorylation upon TCR stimulation in the context of NF-B activation (15). Additional experiments are required to identify the RIP2-dependent phosphorylation site(s) in Bcl10 and to assess whether RIP2-mediated Bcl10 phosphorylation contributes to the effect on the actin cytoskeleton described here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the pan-PKC inhibitor GFX did not affect the Ser 138 -dependent initial phosphorylation of Bcl10 nor the TCR-induced F-actin increase, but showed an inhibitory effect on a second, as yet unidentified site of Bcl10 phosphorylation that is thus unlikely to be relevant for actin polymerization. The receptor-interacting protein (RIP) family kinase RIP2 has been shown to associate with Bcl10 and to induce its phosphorylation upon TCR stimulation in the context of NF-B activation (15). Additional experiments are required to identify the RIP2-dependent phosphorylation site(s) in Bcl10 and to assess whether RIP2-mediated Bcl10 phosphorylation contributes to the effect on the actin cytoskeleton described here.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genetic evidence of a role for RIP2 has recently been reported in T-cell signaling (Ruefli-Brasse et al, 2004). RIP2 associates with BCL10 and is necessary for TCR-induced BCL10 phosphorylation and IKK activation.…”
Section: Role Of Nf-jb In the Adaptive Responsementioning
confidence: 99%
“…The two initial reports on Rip2 À/À mice mentioned above suggested that these mice had intrinsic defective Th1 immune responses and that Rip2 was required for optimal activation of NF-kB and T-cell proliferation upon TCR stimulation [6,27]. Rip2 was shown to associate with Bcl10, a signaling molecule of the TCR-induced NF-kB pathway, after T-cell stimulation [30]. The same group also reported a delayed allograft rejection of neonatal heart tissue in Rip2-deficient mice, suggesting impaired adaptive immunity in the absence of Rip2 [30].…”
Section: Introductionmentioning
confidence: 99%
“…Rip2 was shown to associate with Bcl10, a signaling molecule of the TCR-induced NF-kB pathway, after T-cell stimulation [30]. The same group also reported a delayed allograft rejection of neonatal heart tissue in Rip2-deficient mice, suggesting impaired adaptive immunity in the absence of Rip2 [30]. More recently, using fully backcrossed animals, other reports failed to identify intrinsic defects of the adaptive immune system in Rip2-deficient mice [31,32].…”
Section: Introductionmentioning
confidence: 99%